Native and activated antithrombin inhibits TMPRSS2 activity and SARS‐CoV‐2 infection. Issue 1 (16th September 2022) - Wettstein, Lukas; Immenschuh, Patrick; Weil, Tatjana; Conzelmann, Carina; Almeida‐Hernández, Yasser; Hoffmann, Markus; Kempf, Amy; Nehlmeier, Inga; Lotke, Rishikesh; Petersen, Moritz; Stenger, Steffen; Kirchhoff, Frank; et al.
Abstract: Host cell proteases such as TMPRSS2 are critical determinants of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) tropism and pathogenesis. Here, we show that antithrombin (AT), an endogenous serine protease inhibitor regulating coagulation, is a broad‐spectrum inhibitor of coronavirus infection. Molecular docking and enzyme activity assays demonstrate that AT binds and inhibits TMPRSS2, a serine protease that primes the Spike proteins of coronaviruses for subsequent fusion. Consequently, AT blocks entry driven by the Spikes of SARS‐CoV, MERS‐CoV, hCoV‐229E, SARS‐CoV‐2 and its variants of concern including Omicron, and suppresses lung cell infection with genuine SARS‐CoV‐2. Thus, AT is an endogenous inhibitor of SARS‐CoV‐2 that may be involved in COVID‐19 pathogenesis. We further demonstrate that activation of AT by anticoagulants, such as heparin or fondaparinux, increases the anti‐TMPRSS2 and anti‐SARS‐CoV‐2 activity of AT, suggesting that repurposing of native and activated AT for COVID‐19 treatment should be explored.